Intrinsic Functional and Structural Brain Connectivity in Humans Predicts Individual Social Comparison Orientation - Jung, Wi Hoon; Kim, Hackjin (Frontiers in Psychiatry, 2020)
Social comparison orientation (SCO), the tendency to compare oneself with others, is universal, varies widely across individuals, and predicts important life and health outcomes. However, the neural mechanism underlying individual differences in SCO is still not well-understood. In the present study, we identified intrinsic neural markers of SCO in healthy young adults (n = 42) using a multimodal neuroimaging approach that included diffusion tensor imaging and resting-state functional MRI data. We found that higher SCO was associated with weaker structural and functional connectivity (SC and FC) strengths between the ventral striatum and the medial prefrontal cortex, which are core regions of the brain reward network. Additionally, individual SCO was negatively associated with neural fluctuations in the intraparietal sulcus (IPS), part of the frontoparietal network, and positively with FC between the IPS and anterior insula/amygdala cluster. This finding was further confirmed by the observation of independently-defined, large-scale, inter-network FC between the frontoparietal network and cingulo-opercular network. These results show how the intrinsic functional and structural architecture of the brain is linked to individual differences in SCO, providing novel evidence for an association between individual SCO and the brain’s various networks.